Pengembangan Knowledge Management System pada Bina Nusantara Berbasis Microsoft Sharepoint 2010 - Karto Iskandar (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The role of knowledge in an effort to developing and maintaining an organization has been strong regarded as a very important asset. Bina Nusantara is an organization that puts the human resources and paperwork as the main resource to perform maintenance on existing Knowledge. The problems that occur in Bina Nusantara is the high turnover rate leads to knowledge walkout. The purpose of this study is to design and implement features of Knowledge Management System (KMS) in Bina Nusantara organization specifically to facilitate knowledge capture, knowledge sharing, and document knowledge to nurture the development of knowledge that occurs in the environment Bina Nusantara. KMS is expected to prevent the knowledge walkout that due to the high turnover rate at Bina Nusantara. The methodology used in this study is the use of literature study and application design for KMS using Microsoft SharePoint 2010 technology. The conclusion of this study is to take advantage of features available in Microsoft SharePoint 2010 as a KMS media at Bina Nusantara become more optimal and easy Knowledge document search.